(untitled) (Nuntius Antiquus, 2011)
As usually occurs in Plautus’ comedy, in Casina the search for pleasure is an important motif of the plot. However in this play pleasure is represented – whether figuratively, whether more directly – in a particular mood. Besides a very recurrent use of metaphors and images related to scents and flavoring, there are notorious much more explicit (and not so commonly found in Plautine texts) mentions to the erotic desire and sexual intercourse. Evincing the uarietas in which pleasure is referred to in Casina, this article aims to reflect on how such a representation affects the composition of the Plautine plot. In Casina some sexual references also contribute to allude to another kind of pleasure: the one that comes from theater, represented in this comedy by a play-within-a-play.